2015
DOI: 10.1177/0961203315608254
|View full text |Cite
|
Sign up to set email alerts
|

Association of BAFF, APRIL serum levels, BAFF-R, TACI and BCMA expression on peripheral B-cell subsets with clinical manifestations in systemic lupus erythematosus

Abstract: Decreased BCMA expression on peripheral B cells according to severe disease activity suggests that BCMA plays an important regulating role in B-cell hyperactivity and immune tolerance homeostasis in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 47 publications
6
82
1
Order By: Relevance
“…The pathways through which GC B cell tolerance break down are not clear, but in mouse models it was recently shown that IFN-γR signaling in B cells as well as B cell IFN-γ production were critical initial steps for spontaneous GC development leading to autoimmunity6162. Interestingly, SLE patients also display increased BAFF serum levels that correlate with disease activity63. In accordance with this, BAFF blockade (belimumab) is the first U.S. Food and Drug Administration-approved treatment of SLE using a biologic.…”
Section: Discussionmentioning
confidence: 99%
“…The pathways through which GC B cell tolerance break down are not clear, but in mouse models it was recently shown that IFN-γR signaling in B cells as well as B cell IFN-γ production were critical initial steps for spontaneous GC development leading to autoimmunity6162. Interestingly, SLE patients also display increased BAFF serum levels that correlate with disease activity63. In accordance with this, BAFF blockade (belimumab) is the first U.S. Food and Drug Administration-approved treatment of SLE using a biologic.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum levels of the cytokines B lymphocyte stimulator (BLyS) and APRIL in SLE patients correlate with both disease activity (11,12) and autoantibody production (13)(14)(15)(16). These factors are therefore promising targets for new investigational therapies.…”
mentioning
confidence: 99%
“…We chose the following six genes for their potential role in the innate response: TNFSF13, PIK3R1, NFATC1, FES, TCF7 and RORA . The TNF superfamily 13, or APRIL, protein is a surface or secreted ligand recognized by the transmembrane activator and calcium-modulating cyclophilin ligand interactor (TACI) and B-cell maturation antigen (BCMA) receptors and has been implicated in the pathogenesis of numerous pro-inflammatory conditions such as rheumatoid arthritis [56], atherosclerosis [57], lupus [58] and psioriasis [59]. Moreover, APRIL has been shown to activate NF-κB dependent cytokine production in macrophages [60] and keratinocytes [59].…”
Section: Discussionmentioning
confidence: 99%